Zorotypus novobritannicus n. sp., the first species of the order Zoraptera (Zorotypidae) from the Australasian Ecozone - Terry, Matthew D.; Whiting, Michael F. (Zootaxa, 2012)
Zorotypus novobritannicus n. sp. (Polyneoptera: Zoraptera: Zorotypidae) is described from the Australasian ecozone frommales and females of both apterous and dealated morphs. The description includes detailed accounts of head and thoraxof the eyeless apterous morphs, head of the dealated winged morph with both eyes and ocelli, and the male and femaleabdomen and terminalia. Zorotypus novobritannicus n. sp. has unique, palmate setae on the lateral and ventral sides of thecerci of both sexes and dealated winged morphs are found at much higher densities than have been reported for any other species of Zoraptera.